Fracture of the Anterior Maxillary Alveolar Ridge with Laryngoscopy - Nishioka, Gary J. (1986)
The following case report describes a patient who suffered an anterior maxillary alveolar ridge fracture resulting from difficult laryngoscopy and intubation. An unfortunate sequelae of this injury was the loss of two maxillary central incisors due to persistent mobility despite long term dental stabilization. To the authors' knowledge, fractures involving the premaxilla have not been reported as a complication of laryngoscopy and intubation.